Rabies Outbreak in the Urban Area of Delhi: An Investigation Report and One Health Perspective for Outbreak Management - Monil Singhai; Vishesh Sood; Girraj Singh; Cordelia Siddiqui; Tushar Nale; Prabhakar Jha; Priyanka Yadav; Rekha Jaiswal; Manju Bala; Sujeet K. Singh; Simmi Tiwari (MDPI AG, 2022)
Rabies is a global problem and is endemic in India. Rabies cases occur throughout the year, and the majority of cases are associated with dog bites. We report a rabies outbreak investigation in an urban area of Delhi conducted by our multidisciplinary team, and its role in proactively controlling a rabies outbreak by concerted efforts and timely advice to various stakeholders using a "One Health Approach." A veterinary care NGO from Delhi picked up a suspected rabid stray dog and submitted a brain sample for diagnosis of rabies, as they had received information from a resident of the locality about an unprovoked animal bite incident involving a girl (category III bite) and close contact of two more stray dogs living in the vicinity of the suspected rabid dog. The laboratory diagnosis of rabies in the suspected dog brain sample was confirmed by using Fluorescence Antibody Test (FAT). A multi-expert investigation team with expertise in medicine, microbiology, veterinary sciences, laboratory diagnosis, and public health was constituted to investigate the outbreak. The timely, adequate, and appropriate anti-rabies management initiated for the animal bite victims in this incident could prevent rabies. Proactive involvement of multiple stakeholders and knowledge attributes and practice of local residents could prevent human rabies. As there were no further reports of dog bites from the area, the chain of rabies transmission in that area could be controlled. The presented work is a classical case scenario where concerted efforts of all stakeholders achieved effective control and prevention of rabies by adopting the "One Health approach".